Analisis Kontribusi dan Penyerapan Tenaga Kerja Sektor Pertanian di Kabupaten Aceh Utara - Aulia Intani; Ahmad Humam Hamid; Irwan A. Kadir (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
The purpose of this study is to determine the respective contribution of the agriculture, forestry, and fisheries sub-sectors to the agricultural GRDP in North Aceh Regency as well as to see each of the agriculture, forestry and fisheries sub-sector that have the potential to become the basic sub-sector in North Aceh Regency and to find out the role of the agricultural, forestry and fisheries sectors on the absorption of labor in North Aceh Regency. Based on the research results, the sub-sectors of the agriculture, livestock, hunting and agricultural services have the largest contribution value with an average of 15,50 percent. The fisheries sub-sector has changed its position from the basic sub-sector to the non-basic sub-sector in the future because it has a DLQ 1. The doubling rate of the agricultural sector worforce in North Aceh Regency is 1.90, which means that every 1 increase in the agricultural sector workforce, it will be able to create new jobs that increase employment in other economic sectors in North Aceh Regency as much as 1 person with fluctuating employment during 2013-2017.